Analysis of inbreeding depression in eight S1 cassava families - Rojas, M.C.; Pérez Velásquez, Juan Carlos; Ceballos, H.; Baena Garcia, D; Morante, N; Calle, F. (Wiley, 2009)
Inbreeding offers numerous advantages but also presents some problems for the genetic improvement of cassava (Manihot esculenta Crantz). One of the concerns is that inbreeding depression (ID) may be too drastic for (even partially) inbred materials to survive. A large experiment was conducted to quantify ID in cassava. S1 families from eight elite cultivars, each represented mostly by over 90 cloned genotypes, were produced and evaluated in a replicated trial at one location. The results from this evaluation allowed measurement of ID levels for key traits such as fresh root yield (63.9%), fresh foliage yield (37.9%), harvest index (26.5%), plant height (10.1%), and dry matter content in the roots (5.3%). Results also indicated (as expected) that ID, for a given trait, was not uniform among the eight families evaluated. For reasons provided in the article, the ID levels measured in this study may have been overestimated. Compared with the first experiences introducing inbreeding in temperate and tropical maize (Zea mays L.), we concluded that the use of homozygous progenitors in future cassava genetic enhancement is feasible. The average ID and frequency distributions within S1 families for different traits correlated well with the relative importance of nonadditive genetic effects controlling their inheritance as reported in the literature.